EXPLORATORY STUDY ABOUT KNOWLEDGE, ATTITUDE AND PRACTICE ABOUT PHARMACOVIGILANCE AND ADR REPORTING AMONG RESIDENTS OF A TERTIARY CARE TEACHING HOSPITAL - KOTHARI, NITIN; JAIN, ANURAG; CHAWDA, HIREN M.; AGRAWAL, NEERAJ (International Journal of Current Pharmaceutical Research, 2022)
Objective: This study, aimed at investigating the knowledge and attitude of resident doctors about ADR reporting in a tertiary care teaching hospital. Methods: This was a cross-sectional, observational, questionnaire-based study conducted in Shri Krishna Hospital and Medical Research Centre, 550 bed tertiary care teaching rural hospital attached to Pramukhswami medical college, Karamsad, Gujarat. Results: 50 questionnaire forms were analysed, giving a response rate 86.20%. Of the respondents 56% were men, remaining were women. Mean age of the respondents was 25+1.05 y. All but one resident have heard the term ‘pharmacovigilance,’ but 34 out of 50 were able to define it accurately. Twenty participants preferred email for ADR reporting while 14 preferred direct contacts for ADR reporting. Telephone is liked by 9 participants. All residents admitted the importance of pharmacovigilance in unison. Majority of the residents (96%) were in view to teach pharmacovigilance actively to students. Seventeen out of 50 residents were aware about Pharmacovigilance Program of India, a program by Government of India for pharmacovigilance and ADR reporting. 28 residents did not know about any such program. Three residents opined that no specific national program is running and India is following a program undertaken by WHO. The most preferred method of ADR reporting by residents is email/website followed by direct contact. Twenty were in favour of the first method, while 14 preferred the later method. Nine residents selected the telephone method as method of ADR reporting. Conclusion: Today’s residents are future’s consultants. So it is the need of the hour to stimulate residents to report ADRs.